PdO@CoSe2 composites: efficient electrocatalysts for water oxidation in alkaline media. Issue 1 (3rd January 2023) - Hanan, Abdul; Solangi, Muhammad Yameen; Jaleel laghari, Abdul; Shah, Aqeel Ahmed; Aftab, Umair; Ibupoto, Zahoor Ahmed; Abro, Muhammad Ishaque; Lakhan, Muhammad Nazim; Soomro, Irfan Ali; Dawi, Elmuez A.; Al Karim Haj Ismail, Abd; Mustafa, Elfatih; et al.
Abstract : In this study, we have prepared cobalt selenide (CoSe2 ) due to its useful aspects from a catalysis point of view such as abundant active sites from Se edges, and significant stability in alkaline conditions. Abstract : In this study, we have prepared cobalt selenide (CoSe2 ) due to its useful aspects from a catalysis point of view such as abundant active sites from Se edges, and significant stability in alkaline conditions. CoSe2, however, has yet to prove its functionality, so we doped palladium oxide (PdO) onto CoSe2 nanostructures using ultraviolet (UV) light, resulting in an efficient and stable water oxidation composite. The crystal arrays, morphology, and chemical composition of the surface were studied using a variety of characterization techniques, including X-ray diffraction (XRD), scanning electron microscopy (SEM), high resolution transmission electron microscopy (HRTEM), X-ray photoelectron spectroscopy (XPS), and Fourier transform infrared (FTIR) spectroscopy. It was also demonstrated that the composite systems were heterogeneous in their morphology, undergoing a shift in their diffraction patterns, suffering from a variety of metal oxidation states and surface defects. The water oxidation was verified by a low overpotential of 260 mV at a current density of 20 mA cm −2 with a Tafel Slope value of 57 mV dec −1 . The presence of multi metal oxidation states, rich surface edges of Se and favorable charge transport played a leading role towards water oxidation with a low energy demand. Furthermore, 48 h of durability is associated with the composite system. With the use of PdO and CoSe2, new, low efficiency, simple electrocatalysts for water catalysis have been developed, enabling the development of practical energy conversion and storage systems. This is an excellent alternative approach for fostering growth in the field.